Ferromagnetism of iron under pressure to 21.5 GPa. Issue 19 (10th October 2013) - Wei, Qingguo; Gilder, Stuart A.
<x xml:space="preserve">Abstract</x> [1] Computational, Mössbauer, and synchrotron radiation experiments arrive at disparate conclusions regarding the magnetic state of the high‐pressure, hexagonal closed packed, phase of iron, which likely comprises the bulk composition of Earth's inner core. Using a nonmagnetic, moissanite anvil cell together with a superconducting magnetometer, we measured the remanent magnetization of iron in response to applied magnetic fields under pressure up to 21.5 GPa at room temperature. Two independent experiments using different pressure transmission media reveal a higher remanent magnetization at 21.5 GPa than at initial conditions, which could be attributed to a distorted hexagonal closed packed phase grown during the martensitic transition. Upon both compression and decompression, the remanent magnetization of the body centered cubic phase increases several times over initial conditions while the coercivity of remanence remains mostly invariant with pressure.